2010
DOI: 10.1016/j.jcrs.2010.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Rotational stability of a single-piece toric acrylic intraocular lens

Abstract: The acrylic toric IOL was rotationally stable within the first 6 months postoperatively. The photographic and axis analysis method to evaluate stability had high reproducibility and detected small changes in rotation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
50
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(59 citation statements)
references
References 14 publications
6
50
0
3
Order By: Relevance
“…Several studies have shown that both LRI and toric IOL implantation provide good safety, predictability, and efficacy associated with a postoperative improvement in visual acuity (3,22,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) . Such studies, however, made comparisons with control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that both LRI and toric IOL implantation provide good safety, predictability, and efficacy associated with a postoperative improvement in visual acuity (3,22,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36) . Such studies, however, made comparisons with control groups.…”
Section: Discussionmentioning
confidence: 99%
“…(Ahmed, Rocha et al 2010;Gayton and Seabolt 2010;Koshy, Nishi et al 2010;Visser, Ruiz-Mesa et al 2011) In the majority of these studies, PCO did not compromise the visual outcome and a neodymium:YAG posterior capsulotomy was not required. Too few studies have been performed with Rayner toric or Acri.Comfort toric IOLs to evaluate the incidence of PCO.…”
Section: Posterior Capsule Opacificationmentioning
confidence: 96%
“…This may be done with the patient seated at the slitlamp and with a coaxial thin slit turned to 0-180 degrees. (Mendicute, Irigoyen et al 2008;Alio, Agdeppa et al 2010;Koshy, Nishi et al 2010) The www.intechopen.com limbus is than marked at the horizontal position with either a sterile ink pen or a needle. Another technique to mark the horizontal axis is by using a bubble-marker, such as a Nuijts/Lane Toric Reference Marker (ASICO) (Figure 2) or a Bakewell BubbleLevel (Mastel Precision, Rapid City, US), or by using a gravity marker with a calibrated horizontal position, such as the LRI Gravity Marker (Rumex, Sint Petersburg, Florida, US).…”
Section: Marking Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotational stability of toric IOL is an issue of major concern, once proper alignment is critical for compensating corneal cylinder, resulting in good uncorrected vision. Each degree of rotation causes an average loss of cylinder power of approximately 3%; thus, when an IOL rotates 30 degrees there is no astigmatic correction, although there is a change of axis (44,(46)(47)(48)(49)(50)(51)(52)(53)(54)(55) . Articles comparing the use of toric IOL to other astigmatism reducing techniques, such as opposed clear corneal incisions (56) or LRI (57) , are still scanty in number on literature.…”
Section: B) Non-incisional Approachmentioning
confidence: 99%